PENGARUH KONFLIK PEKERJAAN - KELUARGA (WORK – FAMILY CONFLICT) TERHADAP KINERJA PELAYANAN DAN KOMITMEN ORGANISASI MELALUI KELELAHAN (FATIGUE) PADA KARYAWAN TENAGA KEPENDIDIKAN DI BAGIAN AKADEMIK UNIVERSITAS JEMBER - Widayanti, Andri Eko; Sularso, Raden Andi; Suryaningsih, Ika Barokah (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2017)
Abstract: The purpose of this study is to determine the effect of work-family conflict on service performance and organizational commitment through fatigue on the staff of Teaching Staff in the Academic Department of Jember University. This research was conducted at the University of Jember with a population of 167 employees of Education Personnel in the Academic section and a number of students from each faculty. The sampling techniques used are purposive sampling for the employee and accidental sampling for the student respondents. So the sample collected were 82 employees and 82 students. Analytical techniques using Generalized Structured Component Analysis (GSCA). Result of this research: (1) there is no influence between work-family conflict on service performance and organizational commitment directly; (2) but there is an influence between work-family conflict on performance and organizational commitment indirectly through fatigue. So it can be concluded that fatigue is a perfect mediation variable.Keywords: Work-family Conflict, Fatigue, Service Performance, and Organizational Commitment